Genomic diversity, chromosomal rearrangements, and interspecies hybridization in the Ogataea polymorpha species complex. Issue 8 (18th June 2021) - Hanson, Sara J; Cinnéide, Eoin Ó; Salzberg, Letal I; Wolfe, Kenneth H; McGowan, Jamie; Fitzpatrick, David A; Matlin, Kate
Abstract: The methylotrophic yeast Ogataea polymorpha has long been a useful system for recombinant protein production, as well as a model system for methanol metabolism, peroxisome biogenesis, thermotolerance, and nitrate assimilation. It has more recently become an important model for the evolution of mating-type switching. Here, we present a population genomics analysis of 47 isolates within the O. polymorpha species complex, including representatives of the species O. polymorpha, Ogataea parapolymorpha, Ogataea haglerorum, and Ogataea angusta . We found low levels of nucleotide sequence diversity within the O. polymorpha species complex and identified chromosomal rearrangements both within and between species. In addition, we found that one isolate is an interspecies hybrid between O. polymorpha and O. parapolymorpha and present evidence for loss of heterozygosity following hybridization.